A Descriptive Qualitative on Teachers’ Strategies in Teaching Listening Comprehension - rina lukita; rizky gushendra (Indonesian Journal of Integrated English Language Teaching, 2020)
The purpose of this research is to explore the implementation of teachers’ strategies in teaching listening comprehension. There are three English teachers of SMPN 1 Rimba Melintang, who have been selected by purposeful sampling as the participants. However, A descriptive qualitative research was designed to presume the three aspects of teachers’ strategies i.e. teachers’ interpretation of teaching strategies, whilst-teaching, and assessing students listening comprehension. In collecting data, the researchers conducted semi-structured interview in order to gain the deeper information from the participants. The results and analysis of the interviews found that the teachers’ interpretation of strategies were interdependent and interrelated with other skills, which means to decide a strategy is very influential for the learning outcome.  However, the decision of using different strategies might have different results.  The second aspect, the audio-visual media enable the students to hear sounds and notice directly to the intended object, which followed by a group discussion and quizzes for question-answer sessions, that the students response immediately and spontaneously. Finally, the teacher assesses the results of student work by any particular drills, such as, summarizing the materials, noticing main ideas of the talks, doing presentation, and questions and answers.